Perpetės baltų kraštuose I tūkstantmečio viduryje - Astrauskas, Audrius; Gleiznienė, Gražina; Šimėnas, Valdemaras (Archaeologia Lituana, 1999)
Research of the burial monuments of the mid-first millenium A.D. has lately produced substantially more data on Baltictype shoulder-straps which have not yet been widely described in the archeological literature. Although shoulder-straps were worn quite often and extensively in the old times, they are difficult to identify during archeological research. The design and the wearing style of these shoulder-straps is not clear. A belt put over the shoulder could be warn without a belt buckle. Therefore, such shoulder-straps were usually destroyed and could not be recorded archeologically. Archeologists often find just single belt buckles by the right shoulder of a body.The present article deals with only the most adorned and the most complicated type of shoulder-straps, i.e. shoulder-straps with an adornment on the front side which widens downwards and is made up of separate plates in the form of cones, rectangles, squares or trapezium, and a nozzle. Their origin and a more exact date has not been fully identified. All shoulder straps are different and made using different technology, style and ornaments.Shoulder-straps and battle knives-daggers are most often not found in their original places. However, during the exploration of grave No. 23 in the burial ground of Vidgiriai, the shoulder-strap was found in its original place. This made it possible to identify its purpose and wearing style. One more stimulus to gather data on them was a tendency observed in the article on sharp battle knives-daggers (V. Šimėnas, 1996) to put a battle knife-dagger along with a shoulder-strap into the grave; in those graves other shrouds of the same kind were found.Accumulation of these materials involved reviewing Lithuanian, Latvian and East Prussian archeological literature and archives of the main museums. Shoulder-straps have already caught the attention of museum experts and restorators. We have no doubts that shoulder-straps will be repeatedly investigated in various aspects in the future. This especially applies to their production technologies, jewelry making techniques and ornamentation. By 1995, four shoulder-straps had been preserved and reconstructed in Lithuania: from grave No. 23 of Vidgiriai, from grave No. 312 and No. 337 of Marvele, and from grave No. 50 of Plinkaigalis. The preservation and reconstruction of all above-said shoulder-straps was performed by G. Gleiznienė.The catalogue on shoulder-straps includes descriptions of 15 shoulder-straps from 7 burial grounds, sets of finds from the graves in which they were found as well as information on their preservation and restoration. The purpose of 8 more finds and the circumstances in which they were found are not quite clear, therefore, they are only mentioned in the article.It becomes evident from the catalogue that the design of individual shoulder-straps is similar but, nevertheless, has significant differences. The comparison of the shoulder-straps shows that each of them differs in its measurements, ornamentation or technological features. They are obviously done by different craftsmen and on individual orders.Shoulder-straps with numerous adornments are found only in the graves of well-off and rich male warriors. All the shoulder-straps discussed here were found together with a few pieces of jewelry which are easy to date. Table No. 3 contains all known sets of shrouds with shoulder-straps. The main task is to determine extreme limits for dating this group of items. Research has shown that shoulder straps could first appear at the turn of the C3-D period or at the end of the 4th century or the beginning of the 5th century. According to the shroud sets, the earliest shoulder-straps can be identified as those from grave No. 13 of Kalniškiai and No. 47 and No. 56 from Žviliai grave. Chronological research shows that shoulder-straps were worn for a very short period of time, i.e. until the middle of the 6th century. This way, their dating has been made more accurate and detailed and they could become good chronological indicators. It is already becoming evident that the emergence of shoulder-straps could he dated to a later period and be linked with the emergence of a whole complex of new technologies.While charting places where shoulder-straps have been found, it becomes clear that they were common in a clearly defined area. This makes it possible to say that they most probably reflect certain ethnic processes. The map shows that shoulder-straps, like sharp battle knives-daggers are found by the Lithuanian seaside, by the River Nemunas up to the town of Kaunas, in the basin of the Nevėžis river and in the peninsula of Semland. These lands are situated closer to waterways (the see, the lagoon and the River Nemunas). There are no such shoulder-straps in Latvia and Northern and Eastern Lithuania and North East Poland.The issue of the emergence and origin of shoulder straps is rather problematic. Some researchers say that they are a local product, others believe that they were imported. In Western European archeological literature, opinion that shoulder-straps were an element of the armaments in the barbarian world most often prevails. Shoulder-straps could have originated on the border of the Barbarian and Roman Empire where barbarian and Roman elements of armaments clashed. The most probable region of this influence is the middle reaches of the River Danube and the coast of the Black Sea. The shoulder-straps discussed in the article must have originated locally, however their making technologies do not have local roots.Shoulder-straps can tell a lot about the social status of the people who we wearing them. Researchers have noticed that they are usually found in the graves of very rich horsemen warriors. Sets of shrouds show that these graves contain a lot of weapons and jewelry with the amplitude of silver items being the most prominent feature.